(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2024)
The lament for the end of utopia which expresses the futuristic novel, Cría Terminal (2014), exposes the crisis of an ethical ideal: the loss of the possibility of a better world. The bases of the moral contract implicit in the threat of its dissolution in the near future will be the object of investigation of this work, which considers the philosophy of Hans Jonas as the main theoretical reference. Therefore, it will be sought to specify the relationship between the barbarization of culture (with its exemplary behaviors and characters) and the economic-political processes tending to the biotechnological domination of the human environment. The modalizing perspective of the narrative action and intrigue and its adaptation to an ethical interest in establishing an optimal life model for society, disappointed by the technical civilization of the future, will be the subject of analysis.